2010
DOI: 10.1097/mph.0b013e3181dccbf4
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation Syndrome in the Acute Phase of Kawasaki Disease

Abstract: Rare cases of macrophage activation syndrome (MAS) occurring during the acute phase of Kawasaki disease (KD) have been reported. We sought to characterize, review treatment, and outcomes of KD patients with clinical features of MAS. Medical histories of patients treated for KD and MAS between January 2001 and March 2008 were reviewed. Of 638 KD patients seen, 12 (1.9%) had additional clinical findings usually associated with MAS; 7 of them were males older than 5 years (6.1%; odds ratio: 6.8, P=0.002). Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 22 publications
1
45
1
5
Order By: Relevance
“…[7][8][9] There have been few reported cases of MAS in KD. Latino et al 10 reported that 1.9% of KD patients had additional clinical findings of MAS, and 10 out of 12 patients with KD in their series met at least five of the eight criteria necessary for diagnosis of MAS. Treatment beyond the standard KD protocol (aspirin + IVIg) was necessary in all but one patient.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] There have been few reported cases of MAS in KD. Latino et al 10 reported that 1.9% of KD patients had additional clinical findings of MAS, and 10 out of 12 patients with KD in their series met at least five of the eight criteria necessary for diagnosis of MAS. Treatment beyond the standard KD protocol (aspirin + IVIg) was necessary in all but one patient.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which HLH develops in these patients is unknown. Hypercytokinemia, as a result of abnormal immune-regulation, has been proposed to contribute to the pathogenesis of both diseases (2,4).…”
Section: Discussionmentioning
confidence: 99%
“…Hemophagocytic lymphohistiocytosis (HLH), is a systemic inflammatory disorder characterized by uncontrolled histiocytic proliferation, hemophagocytosis, macrophage activation, and up-regulation of inflammatory cytokines, which can complicate the course of KD (2)(3)(4). In most of the reported cases, HLH develop long after treatment or during the recurrent course of the disease (3)(4)(5)(6). Herein we report a case with secondary HLH occurring during the acute phase of fatal KD in a 4 month-old girl.…”
mentioning
confidence: 99%
“…Acute phase reactants [erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP)] are almost always increased. Increased leukocytosis (neutrophil dominant) is frequent (24,25). Thrombocytosis as a characteristic feature of KD usually occurs during the 2 weeks of the illness.…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…Thrombocytosis as a characteristic feature of KD usually occurs during the 2 weeks of the illness. Increased serum transaminase levels, hypoalbuminemia and sterile pyuria are common (24,25).…”
Section: Laboratory Findingsmentioning
confidence: 99%